Tactics of Treatment of Tourniquet Syndrome after Gunshot Wounds - Khoroshun, E.M.; Strafun, S.S.; Shypilov, S.A.; Klapchuk, Yu.V.; Bahrii, O.S.; Honcharenko, S.S.; Kupriianchuk, V.V. (TERRA ORTHOPAEDICA, 2024)
Summary. The objective of our study was to develop a differentiated approach to the treatment of tourniquet syndrome based on the severity and stages of its development. The work was based on a retrospective analysis of 30 wounded with tourniquet syndrome of the upper and lower extremities, who were treated at the Military Medical Clinical Center of the Northern Region. All the wounded were hospitalized from the combat zone; all were males, aged 33.8±0.4 years. After admission to the Military Medical Center of the Northern Region (Role 3), anamnestic data were collected, clinical symptoms as well as laboratory and additional research methods were analyzed. To form a differentiated approach to the treatment of tourniquet syndrome, the analysis of the following indicators was carried out: the duration of the tourniquet (up to 3 hours, 3.1-6 hours, 6.1 hours and more), the place of tourniquet application (shoulder, thigh), local clinical manifestations (edema, paresthesia, hypoesthesia, anesthesia, hypothermia, contracture of the joints of the hand or foot), laboratory indices (creatinine, alanine aminotransferase, aspartate aminotransferase, creatine phosphokinase, potassium, and myoglobin), assessment of peripheral pulse, diuresis, ultrasound examination of muscles, ultrasound examination of the kidneys and inferior vena cava to calculate infusion therapy, radiographic and thermal imaging studies at the site of injury, and intraoperative visual evaluation of the muscles (viable muscles, partial or widespread rhabdomyolysis). Based on the analysis of the obtained data, a classification and treatment algorithm of tourniquet syndrome were developed, which enabled to take a rational approach to the treatment of this category of patients based on determining the severity and stages of its development.